2021
DOI: 10.1111/ina.12957
|View full text |Cite
|
Sign up to set email alerts
|

Study of synergistic disinfection by UVC and positive/negative air ions for aerosolized Escherichia coli , Salmonella typhimurium , and Staphylococcus epidermidis in ventilation duct flow

Abstract: Heating, ventilating, and air-conditioning (HVAC) systems are valuable engineering tools widely adopted in buildings of tropical and sub-tropical climates (such as Hong Kong) where air-conditioning is needed almost all year round to provide comfortable indoor environments. 1 Furthermore, HVAC systems are a means of controlling indoor air quality. However, empirical evidence indicates that HVAC systems may also become potential sources of bioaerosols through entrainments induced by airflow when the filter or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…alcaligenes had the highest susceptibility among the four tested bacteria for 222 and 254 nm UV wavelengths. This finding was also reported in previous measurements, , and it could be attributed to the thicker cell walls of gram-positive bacteria when compared with gram-negative bacteria. , …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…alcaligenes had the highest susceptibility among the four tested bacteria for 222 and 254 nm UV wavelengths. This finding was also reported in previous measurements, , and it could be attributed to the thicker cell walls of gram-positive bacteria when compared with gram-negative bacteria. , …”
Section: Resultssupporting
confidence: 89%
“…It was observed that S. epidermidis gave the least susceptibility to UV irradiation, while P. alcaligenes had the highest susceptibility among the four tested bacteria for 222 and 254 nm UV wavelengths. This finding was also reported in previous measurements, 7,38 and it could be attributed to the thicker cell walls of gram-positive bacteria when compared with gram-negative bacteria. 39,40 Furthermore, it can be found that bacteriophage P22 was less susceptible to both 222 and 254 nm UV irradiation than the tested bacteria.…”
Section: Susceptibility Of Airborne Microorganismsmentioning
confidence: 92%
“…Negative ions gain hydrogen from surface molecules of pathogens due to electrostatic force. The elimination of hydrogen from or the disruption of the surface molecules of pathogens results in inactivation (Nunayon et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that negative ions could disinfect a wide variety of aerosolized microorganisms, including Salmonella typhimurium (Nunayon et al, 2022), Staphylococcus epidermidis (Kim et al, 2011;Lee et al, 2014;Nunayon et al, 2022), Serratia marcescens , Escherichia coli (Huang et al, 2008;Park et al, 2009;Kim et al, 2011), Bacillus subtilis (Huang et al, 2008), Aspergillus niger, and Aspergillus versicolor (Huang et al, 2008). Escombe et al (2009) found that negative air ionization prevented most airborne Mycobacterium tuberculosis transmission detectable by guinea pig air sampling.…”
Section: Introductionmentioning
confidence: 99%
“…There are stationary strains. Disputes do not form (Nunayon et al, 2022). Escherichia coli is heat-resistant and can survive in the wild for several months (Lim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%